Prosthodontic rehabilitation of dentinogenesis imperfecta - Anil Goud; Saee Deshpande (Contemporary Clinical Dentistry, 2011)
Dentinogenesis imperfecta and its prosthodontic management is a challenging task. Treatment protocol varies according to clinical case. Although various reports in the literature suggest general guidelines for treatment planning, the present case report describes a full mouth rehabilitation of a young patient with dentinogenesis imperfecta treated by maxillary fixed partial dentures and mandibular fiber reinforced overdenture with metal occlusal surfaces.